Urban Governance: An Overview - Chinyere, Nebo Lilian; Jacinta, Oko Onyinyechi; Anyim, Ngosi Annastecia (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
The entire developing world is witness to an unprecedented shift of human settlement to the cities. While Nigeria’s population remains substantially rural, the numbers of people living in the urban area are steady on the increase. The economic base of the nation through expanding industries, trade, commerce and services has already shifted to urban centres. Urban governance as an issue has assumed critical importance in the context of the ever-growing role of urban centres in the overall economic growth, employment generation and contribution such centers make to the rational and state wealth. With urban centers growing rapidly, urban governance becomes crucial especially on the impact it has on the life and liberty of the innumerable urban dwellers. With cities becoming centres for a large investment, specialized services, amenities and their effective and efficient functioning assume added importance. If urban centers have been termed as engines of economic growth, urban governance can rightly be called wheels of such engines. In this study, the expository method has been adopted to understand urban governance with Nigeria as a case study.